Survival and prognostic factor analysis in whole brain irradiation of patients with brain metastases - (:unkn) unknown (My University, 2001)
Objective: The aim of the study was to analyse the survival results in patients with brain metastases treated by whole brain external radiotherapy and determine the prognostic factors affecting survival. Methods: Eighty-three patients with brain metastases were treated by external radiotherapy. Before irradiation 21 had metastatectomy, 4 had stereotactic radiosurgery and 4 had stereotactic biopsy for diagnosis. The primary tumor was controlled in 39 patients (47%), 30 (36%) had metastases other than brain. Whole cranial irradiation was performed on all patients by a linear accelerator with 6 MV energy. Results: Median follow-up for all patients was 14 weeks (1-143 weeks). Median overall survival and 1 year survival for the whole group was 14 weeks and 25%, respectively. Cranial progression free survival was median 40 weeks. In multivariate analysis Karnofsky Performance Scale score, gender and metastatectomy / radiosurgery were found to be independent prognostic factors. Conclusion: External radiotherapy is an efficient treatment modality for palliation and stabilizing cranial progression in patients with brain metastases. Better survival results are obtained in younger, solitary metastatic patients with good performance status and controlled systemic disease when metastatectomy or radiosurgery added.
Keywords: Brain metastases; Prognostic factors; Radiotherapy